2012
DOI: 10.1159/000339409
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Anti-Neutrophil Cytoplasmic Antibody-Positive Disease Complicating Subacute Bacterial Endocarditis: To Treat or Not to Treat?

Abstract: A 54-year-old man was diagnosed with Streptococcus mutans endocarditis of the mitral valve. Serological tests disclosed the presence of multiple autoantibodies including c-ANCA, anti-PR3 and anti-MPO. While the fever subsided with antibiotics, mental status and renal function deteriorated rapidly. Kidney biopsy revealed pauci-immune glomerulonephritis and acute eosinophilic interstitial nephritis. The abnormal clinical features improved rapidly after addition of corticosteroids and cyclophosphamide to the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 14 publications
0
29
0
1
Order By: Relevance
“…La literatura recoge 16 casos de ANCA positivos en pacientes con endocarditis y glomerulonefritis aguda en biopsia renal (Tabla 1), de los cuales diez son ANCA anti-PR3 positivos [5][6][7][8][9][10][11][12][13] , dos anti-mieloperoxidasa 11,14 y en cinco de ellos no se especifica el tipo [15][16][17][18][19] . Los ANCA anti-PR3 se pueden elevar en enfermedades del tejido conectivo e infecciones crónicas como endocarditis subagudas bacterianas, tuberculosis o infección por el virus de la hepatitis B o C 5 , así como en ancianos.…”
Section: Discussionunclassified
“…La literatura recoge 16 casos de ANCA positivos en pacientes con endocarditis y glomerulonefritis aguda en biopsia renal (Tabla 1), de los cuales diez son ANCA anti-PR3 positivos [5][6][7][8][9][10][11][12][13] , dos anti-mieloperoxidasa 11,14 y en cinco de ellos no se especifica el tipo [15][16][17][18][19] . Los ANCA anti-PR3 se pueden elevar en enfermedades del tejido conectivo e infecciones crónicas como endocarditis subagudas bacterianas, tuberculosis o infección por el virus de la hepatitis B o C 5 , así como en ancianos.…”
Section: Discussionunclassified
“…The majority of the patients had positive c-ANCA and/or anti-PR3 serologies. Four patients had positive c-ANCA and elevated titers of both anti-PR3 and anti-MPO antibodies [36,48]. Two patients had elevated titers of all four ANCA antibodies [34].…”
Section: Laboratory Testsmentioning
confidence: 94%
“…Immunofluorescence findings were reported in 19 patients. Electron microscopy findings were reported in only four patients [29,44,48,50]. Table 9 shows the histological diagnoses of renal pathology.…”
Section: Renal Manifestationsmentioning
confidence: 99%
“…In a case series, PR3‐ANCA and associated small vessel vasculitis (SVV) developed in patients with infective endocarditis (IE) caused by Enterococcus faecalis , Streptococcus mutans , Streptococcus oralis and Bartonella henselae . It was concluded that with some infective agents, subacute and/or chronic inflammatory states including infective endocarditis, may induce formation of auto‐antibodies, such as ANCA, which may in turn carry some cross‐reactivity with immune components or endothelial cells, and yield vessel wall damage and vasculitis …”
Section: Pathogenesismentioning
confidence: 98%
“…Humoral and cellular immune response may also play a role in some forms of infection‐associated vasculitides. Increased production of IgA, IgA1 and impaired glycosylation of IgA1 have been reported in IgA vasculitis associated with C. difficile and M. pneumoniae , although the immune mechanisms leading to these changes have not been elucidated . In a case series, PR3‐ANCA and associated small vessel vasculitis (SVV) developed in patients with infective endocarditis (IE) caused by Enterococcus faecalis , Streptococcus mutans , Streptococcus oralis and Bartonella henselae .…”
Section: Pathogenesismentioning
confidence: 99%